Uso de selección asistida con marcadores para resistencia a antracnosis en frijol común - Garzon Gutierrez, LN; Blair, Matthew W.; Ligarreto Moreno, GA (2007)
The anthracnose caused by Colletotrichum lindemuthianum is one of the most significant diseases in beans (Phaseolus vulgaris L.) and can produce yield losses up to 95%. In this study, a breeding program utilizing molecular marker assisted selection (MAS) was initiated. In order to obtain commercial Colombian climbing beans resistant to C. lindemuthianum, the program incorporated genes Co-5 and Co-42 taken from G2333, a resistant Mesoamerican cultivar. From the crosses between G2333 and seven cultivated Andean beans, were obtained progenies BC1F1. The cultivated Andean beans included Bola roja and Rojo moteado types gathered from Cundinamarca and Boyacá crops. The BC1F1 plants were selected using the SCARs molecular markers SAB3 and SAS13 linked to Co-42 and Co-5 genes, respectively. In a genotypic evaluation of 1.271 BC1F1 plants, 608 and 603 were amplified with SAB3 and SAS13, respectively. The segregation expected ratio (1:1) in X2 tests was obtained for each molecular marker indicating X2 = 2,38, P = 0,12 for SAB and X2 = 33,32, P = 0,07 for SAS13. The amplification with both molecular markers was obtained in 299 plants BC1F1, according to the expected ratio (X2 = 1,11, P = 0,78) adjusted to the independent segregation. These plants were selected to continue the breeding program. In this study, a molecular marker assisted selection was implemented and introduction of resistant genes into commercially important Colombian beans was accelerated.